Optogenetic Modification of Glycerol Production in Wine Yeast - Cubillos-Riffo, F (American Chemical Society, 2025)
The wine strains of Saccharomyces cerevisiae transform glucose into ethanol and other byproducts such as glycerol and acetate. The balance of these metabolites is important during the fermentation process, which impacts the organoleptic properties of wines. Ethanol and glycerol productions are mainly controlled by the ADH1 and GPD1 genes, which encode for the alcohol dehydrogenase and glycerol-3-phosphate-dehydrogenase enzymes, respectively. Genetic modification of these genes can thus be used to alter the levels of the corresponding metabolites and to reroute fermentation. In this work, we used an optogenetic system named FUN-LOV (FUNgal-Light Oxygen Voltage) to regulate the expression of ADH1 and GPD1 in a wine yeast strain using light. Initially, we confirmed the light-controlled expression of GPD1 and ADH1 in the engineered strains via RT-qPCR and a translational reporter, respectively. To characterize the generated yeast strains, we performed growth curve assays and laboratory-scale fermentations, observing phenotypic differences between illumination conditions that confirm the optogenetic control of the target genes. We also monitored glucose consumption and ethanol and glycerol productions during a fermentation time course, observing that the optogenetic control of GPD1 increased glycerol production under constant illumination without affecting ethanol production. Interestingly, the optogenetic control of ADH1 showed an inverted phenotype, where glycerol production increased under constant darkness conditions. Altogether, our results highlight the feasibility of using optogenetic tools to control yeast fermentation in a wine yeast strain, which allows changing the balance of metabolic products of interest in a light-dependent manner. © 2025 The Authors. Published by American Chemical Society.